2007
DOI: 10.1007/s10751-008-9611-2
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of nuclear quadrupole interactions in the molecular solid BF3 and the nature of binding between the molecules

Abstract: The electronic structures and nuclear quadrupole interactions (NQI) of the 19 F* (I = 5/2) state of 19 F nucleus in solid BF 3 are studied using the first-principles Hartree-Fock-Roothaan procedure including many-body electron correlation effects. The calculated NQI parameters, 19 F* quadrupole coupling constant (e 2 qQ) and asymmetry parameter η, were found to be in satisfactory agreement with experiment for the solid state system, which gives confidence in the reliability of the calculated electronic structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In the present work, as in our other recent investigations on BF 3 systems [2,3], we have used first principles variational Hartree-Fock-Roothaan procedure [4] combined with Many Body Perturbation Theory [5] for inclusion of electron correlation effects to investigate both the binding or dissociation energy of the complex and the 19 F* NQI parameters [6]. The latter are not currently available but can be measured by the Time Dependent Perturbed Angular Distribution (TDPAD) technique which has already been applied [7] to the BF 3 •NH 3 complex and BF 3 in solid state.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…In the present work, as in our other recent investigations on BF 3 systems [2,3], we have used first principles variational Hartree-Fock-Roothaan procedure [4] combined with Many Body Perturbation Theory [5] for inclusion of electron correlation effects to investigate both the binding or dissociation energy of the complex and the 19 F* NQI parameters [6]. The latter are not currently available but can be measured by the Time Dependent Perturbed Angular Distribution (TDPAD) technique which has already been applied [7] to the BF 3 •NH 3 complex and BF 3 in solid state.…”
supporting
confidence: 77%
“…Since our results for BF 3 -NH 3 system, where convergence with respect to the size of variational basis sets for the dissociation energy and NQI parameters have been tested carefully and shown that the results for (6-311G) basis set including (3df, 3pd) polarization functions [8] are most reliable, we have chosen this basis set for our investigations on BF 3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results for the 19 F* NQI parameters are of course for the solid state systems while our calculated results are for the free molecules of BF 3 and the four complexes. But as we have shown in the paper from our group [8] on solid BF 3 , there are only small differences between e 2 qQ/ h and η for the free molecule and solid BF 3 . One therefore expects similar small differences in the case of the free complexes and corresponding solid state systems.…”
Section: Resultsmentioning
confidence: 51%
“…Finally we calculate the NQI parameters at the excited 19 F* nucleus in the free BF 3 molecule and the four BF 3 ·NH x (CH 3 ) 3−x (x = 0,1,2,3) complexes. The electric field gradient tensor [8] (EFG) is obtained from our calculated wavefunctions and diagonalized to obtain the principal axis components, V xx , V yy , and V zz , where convention dictates that |V zz | > |V yy | > |V xx |. The EFG tensor is then represented by two parameters, the largest component q = V zz which is used to obtain the nuclear quadrupole coupling constant e 2 qQ/ h, and the asymmetry parameter η = (V xx − V yy )/V zz .…”
Section: Methodsmentioning
confidence: 99%